Against all odds: the role of “community cultural wealth” in overcoming challenges as a Black African woman - Nkambule, Thabisile (South African Journal of Higher Education, 2016)
Academic challenges for students from ‘previously disadvantaged backgrounds’ do not necessarily begin in the university but start during the school years, as was the case for the author. This paper is in three parts. Firstly, I present a brief narration of challenges faced before I went to university, which influenced my undergraduate progress. Secondly, I describe key challenges experienced as an undergraduate in particular courses and in a postgraduate education course. Thirdly, I focus on challenges encountered during my first work experience as a Black African PhD student and tutor on an education campus. In particular, I focus on key challenging incidents and how I approached and engaged with them to enable a successful journey through the university as a student and young academic staff member. In the form of first person narration, the qualitative research method of ‘testimony’ is used to reflect critically on my academic and professional journeys as a Black African woman in the post-apartheid era. Testimony was chosen because it provides an epistemic lens to support an analytical inquiry into experiences and intellectual understanding of self and community. Keywords: community cultural wealth; challenges; Black African woman; education; odds; overcome